2023
DOI: 10.1177/17562848231151293
|View full text |Cite
|
Sign up to set email alerts
|

Use of imaging modalities for decision-making in inflammatory bowel disease

Abstract: Cross-sectional magnetic resonance enterography (MRE) and intestinal ultrasonography (IUS) provide valuable and noninvasive information to accurately assess disease activity, severity, and extent; detect complications; and monitor the response to treatment, as well as predict the postoperative recurrence of Crohn’s disease and a negative disease course. Therefore, both imaging modalities are emerging as pivotal diagnostic tools to achieve the emerging therapeutic target of transmural healing associated with be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 80 publications
0
10
0
1
Order By: Relevance
“…Although previous studies have demonstrated an excellent agreement between IUS and MRE in the detection of bowel lesions, it is challenging for different modalities to define TH by a consistent definition. 31 33 Because the definitions of TH varied in different studies, an appropriate and consistent definition of TH should be developed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have demonstrated an excellent agreement between IUS and MRE in the detection of bowel lesions, it is challenging for different modalities to define TH by a consistent definition. 31 33 Because the definitions of TH varied in different studies, an appropriate and consistent definition of TH should be developed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although IUS is less accurate in exploring some parts of the intestinal tract, especially the proximal small bowel, it has significant advantages compared to MRE in terms of greater availability, lower costs, minor invasiveness, and greater patient acceptability. Indeed, IUS does not require fasting or intravenous (iv) administration of gadolinium, avoiding some gadolinium-associated risks, such as allergic reactions, renal complications, and gadolinium retention in the brain) [ 7 ]. A recent French study investigated the burden of monitoring instruments on 916 IBD patients by administering a visual analog scale questionnaire.…”
Section: Intestinal Ultrasoundmentioning
confidence: 99%
“…They describe how these techniques are accurate in assessing disease activity, extent, severity, and complications. They also underline the crucial importance of identifying imaging markers able to predict disease course [ 7 ]. Based on such considerations, research has begun to investigate the utility of cross-sectional imaging not only in monitoring but also in predicting pharmacological treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, its diagnostic accuracy approaches that of more elaborate conventional radiological examinations like MRE. 17,18 It is worth noting that other studies have already demonstrated the efficacy of clinical decision-making involving IUS findings in reducing inflammation in patients with IBD, 19 and IUS is increasingly finding application in CD management, [20][21][22] underscoring its potential utility as a pivotal tool in striving for transmural remission. Inflammatory bowel disease gastroenterologists should be encouraged to consider transmural remission as a viable treatment goal for CD management.…”
mentioning
confidence: 99%
“…IUS not only allows the assessment of disease activity and response to treatment but also predicts long‐term endoscopic activity of disease 16 . Furthermore, its diagnostic accuracy approaches that of more elaborate conventional radiological examinations like MRE 17,18 . It is worth noting that other studies have already demonstrated the efficacy of clinical decision‐making involving IUS findings in reducing inflammation in patients with IBD, 19 and IUS is increasingly finding application in CD management, 20–22 underscoring its potential utility as a pivotal tool in striving for transmural remission.…”
mentioning
confidence: 99%